Republic of Latvia : First Post-Program Monitoring Discussions. (IMF Staff Country Reports; Country Report ;, 2012)
This collection of papers presents the First Post-Program Monitoring Discussions focusing on economic development in the Republic of Latvia. Latvia successfully completed its EU-IMF-supported program in December 2011. As part of the program, Latvia implemented fiscal consolidation measures of more than 15 percent of GDP. Executive Directors have welcomed Latvia's economic recovery since the crisis. Directors have commended the remarkable fiscal consolidation and have also emphasized the need for continued prudence to maintain fiscal and debt sustainability.